DEVELOPMENT AND DISSEMINATION OF A SOCIAL MEDIA-BASED E-LEAFLET FOR PREOPERATIVE PATIENT EDUCATION ON THE PREVENTION OF POSTOPERATIVE NAUSEA AND VOMITING - Kemal, Naufal Athar Faiq; Astuti, Widuri; Perkasa, Tengku Arief Buana; Sulistyowati; Istarini, Attiya; Ayudia, Esa Indah; Tarigan, Nadir Putra Indra (Universitas Jambi, 2026)
Postoperative nausea and vomiting (PONV) is a frequent complication of general anaesthesia that prolongs recovery, increases the burden of care, and may lead to wound strain, dehydration, and aspiration. Many patients are unaware of this risk and hesitate to report their symptoms, while accessible, evidence-based educational material for the lay public remains scarce. This community service activity aimed to develop an electronic educational leaflet (e-leaflet) on the prevention of postoperative nausea and vomiting and to disseminate it through social media. The activity was carried out in four stages: identifying the educational need, designing the content in a question-and-answer format, developing the material from a scientific literature review followed by expert validation and a lay-readability check, and disseminating the final product through Instagram and TikTok. The resulting product was an eleven-slide visual e-leaflet covering the definition, mechanism, risk factors, consequences, medical prevention, patient preparation, and warning signs of postoperative nausea and vomiting. Expert validation confirmed the scientific accuracy of the content, and lay readers judged the language to be understandable. This activity demonstrates that guideline-based knowledge on PONV can be feasibly translated into an accessible, low-cost digital education product for prospective surgical patients, and lays the groundwork for a subsequent, more rigorous evaluation of its impact on patient knowledge.